Rational Design of Hierarchical Beta Zeolites via Post-Synthesis Treatments and Their Applications - Michał Zieliński; Natalia Matysiak; Ewa Janiszewska (Molecules)
Hierarchical zeolites with micro- and mesoporous frameworks can overcome diffusional limitations of microporous systems. This study investigates the post-synthetic modification of Beta zeolite using different porogeneous agents (NaOH, NH4OH, NH4F) under identical conditions to compare their efficiency in generating mesopores. The effect of treatment time was also examined for NH4OH and NH4F. The modified materials were characterized using physicochemical techniques and evaluated for catalytic performance in acetic acid esterification with alcohols of different sizes and adsorption of methylene blue. All the modifications increased mesoporosity but reduced acidity. NaOH produced the highest mesoporosity but significantly reduced acidity, while NH4F retained the most acidity. Catalytic activity in esterification with methanol depended on acidity, but for larger alcohols (n-butanol, benzyl alcohol), activity was influenced by both acidity and mesoporosity. The NH4OH- and NH4F-modified materials, with lower mesoporosity but higher acidity, exhibited better performance with larger alcohols. In MB adsorption, the adsorption equilibrium rates increased with mesoporosity. The NaOH-modified sample reached equilibrium the fastest due to its superior mesoporosity, while the NH4F-modified sample demonstrated the highest adsorption efficiency owing to its abundant Brønsted acid sites. These findings demonstrate that the choice of modifier affects mesoporosity, acidity, and functional performance, offering insights into tailoring hierarchical zeolites for specific applications.